2019
DOI: 10.3390/md17110612
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogallol-Phloroglucinol-6,6-Bieckol Alleviates Obesity and Systemic Inflammation in a Mouse Model by Reducing Expression of RAGE and RAGE Ligands

Abstract: Ecklonia cava (E. cava) can alleviate diet-induced obesity in animal models, and phlorotannins contained in E. cava help prevent hypertrophy-induced adipocyte differentiation. Receptor for advanced glycation end-products (RAGE) is well known to induce hypertrophy of visceral fat and to trigger inflammation substantially. While the relationship between RAGE and obesity and inflammation has been well-characterized, few studies describe the effects of phlorotannin on RAGE. In this study, we investigated the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Several studies have shown that RAGE is related to obesity. Especially, the adipocytes of obese human show higher RAGE expression than those of the lean human [47] and accumulate RAGE ligands as well in the adipose tissues of HFD and obesity models [48][49][50]. In our study, ECE reduced TLR4, RAGE, and NF-κB expressions in the adipose tissues of HFD-fed mice (Figures 4(c) and 4(d)).…”
Section: Effects Of E Cava Extract On Tlr4 Rage and Nf-κbsupporting
confidence: 56%
“…Several studies have shown that RAGE is related to obesity. Especially, the adipocytes of obese human show higher RAGE expression than those of the lean human [47] and accumulate RAGE ligands as well in the adipose tissues of HFD and obesity models [48][49][50]. In our study, ECE reduced TLR4, RAGE, and NF-κB expressions in the adipose tissues of HFD-fed mice (Figures 4(c) and 4(d)).…”
Section: Effects Of E Cava Extract On Tlr4 Rage and Nf-κbsupporting
confidence: 56%
“…Several studies have suggested that intracellular ROS generation can be increased by MGO; thus, this may play an important role in AGE-RAGE formation [45][46][47]. Furthermore, Deshpande et al reported the ROS-mediated proteolytic cleavage of procaspase-3 in the mitochondria of HUVECs [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were fed different diets as described below and provided drinking water ad libitum for eight weeks. For the first four weeks, mice received either a regular normal fat diet (NFD) or a 45% HFD (Research Diet, USA) adapted from a previous study [ 36 ].…”
Section: Methodsmentioning
confidence: 99%